Continuous local anaesthetic wound infusion of bupivacaine for postoperative analgesia in neonates: a randomised control trial (CANWIN Study). Issue 1 (29th August 2022) - Popat, Himanshu; Angiti, Rajeshwar; Jyoti, Jeewan; Webb, Annabel; Barnes, Elizabeth; Halliday, Robert; Badawi, Nadia; de Lima, Jonathan; Spence, Kaye; Thomas, Gordon; Shun, Albert
Abstract : Objective: To determine the effect of continuous wound infusion of local anaesthetic drug (bupivacaine) on total amount of systemic opioid use in the first 72 hours in newborn infants undergoing laparotomy. Design: A two-arm parallel, open-label randomised controlled trial. Setting: A quaternary newborn intensive care unit. Patients: Infants> 37 weeks of gestation undergoing laparotomy for congenital or acquired abdominal conditions. Interventions: Continuous wound infusion of local anaesthetic (bupivacaine) for the first 72 hours along with systemic opioid analgesia (catheter group) or only systemic opioid analgesia (opioid group). Main outcome: Total amount of systemic opioid used within the first 72 hours post laparotomy. Results: The study was underpowered as only 30 of the expected sample size of 70 infants were enrolled. 16 were randomised to catheter group and 14 to opioid group. The two groups were similar at baseline. There was no significant difference between the groups for the primary outcome of median total systemic opioid use in the first 72 hours post laparotomy (catheter 431.5 µg/kg vs opioid 771 µg/kg, difference −339.5 µg/kg, 90% CIhigh 109, p value 0.28). There was no significant difference between the groups for any of the secondary outcomes including pain scores, duration of mechanical ventilation, time to reach full feeds and duration of hospital stay. There were no adverse events noted. Conclusion: Continuous wound infusion of local anaesthetic along with systemic opioid analgesia is feasible. The lack of a difference in total systemic opioid use in the first 72 hours cannot be reliably interpreted as the study was underpowered. Trial registration number: ACTRN12610000633088.